2020
DOI: 10.1021/acschemneuro.0c00136
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants and Haplotypes of Tryptophan Hydroxylase 2 and Reelin Genes May Be Linked with Attention Deficit Hyperactivity Disorder in Egyptian Children

Abstract: Attention-deficit hyperactivity disorder (ADHD) has been proposed to stem from multiple etiologies, perhaps genetic in nature with biological and psychosocial motivates. Tryptophan hydroxylase 2 (TPH2) and Reelin (RELN) genes may play a key role in triggering ADHD. The purpose of this case-controlled study was to explore the linkage of the genetic variants of TPH2 and RELN genes with ADHD. One hundred Egyptian children with ADHD and 105 age and sex matched controls constituted the study samples. Genotyping was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, TPH2-rs4570625 and TPH2-rs11178997 were reported as risk alleles in a family study ( Walitza et al, 2005 ), but another study performed by Shim et al could not replicate the former ( Shim et al, 2010 ). TPH2 rs11179027 and TPH2 rs1843809 alleles are linked with the genetic predisposition to ADHD in Egyptian children ( Abo El Fotoh et al, 2020 ). The T allele (rs1843809), A allele (rs1386493), and G allele (rs1007023) have been associated with ADHD in the United Kingdom population ( Brookes et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, TPH2-rs4570625 and TPH2-rs11178997 were reported as risk alleles in a family study ( Walitza et al, 2005 ), but another study performed by Shim et al could not replicate the former ( Shim et al, 2010 ). TPH2 rs11179027 and TPH2 rs1843809 alleles are linked with the genetic predisposition to ADHD in Egyptian children ( Abo El Fotoh et al, 2020 ). The T allele (rs1843809), A allele (rs1386493), and G allele (rs1007023) have been associated with ADHD in the United Kingdom population ( Brookes et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that no differences were seen in the current study because there was no deficiency in TRP, or 5-HT in the sample. Previous work has linked changes in the TRP2 genes to ADHD [ 37 , 38 ] but in large UK samples and European samples this link was not found [ 92 , 93 ]. Additionally, dietary data indicates that those with ADHD can have normal levels of dietary TRP, meaning that there may not be a deficiency that can be reversed with TRP loading [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, there is evidence that administration of exogenous TRP results in a rise in brain TRP and 5-HT synthesis within the brain [32], which in turn has been shown to result in increased PLOS ONE release of 5-HT in various areas of the brain [33]. Research to date has indicated that lower levels of TRP may be associated with ADHD, at least in adults [34][35][36] and the gene responsible for encoding tryptophan hydroxylase 2 (TPH2), critical for synthesis of central serotonin, has been linked to ADHD symptoms [37,38] as well as performance on standardised laboratory tests of attention [39]. Moreover, tryptophan transport mechanisms have also been found to be altered in ADHD, which could result in lower 5-HT levels [40].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that disturbances in fear-learning systems may be a common gateway to the development of basic mental disorders [63][64][65]. Both the reelin and tryptophan-kynurenine pathways can be genetically linked and negatively correlated [66].…”
Section: Possible Research Regarding the Reelin Signaling Pathwaymentioning
confidence: 99%